1980
DOI: 10.1002/fam.810040305
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation of toxicity caused by combustion of building materials

Abstract: This paper presents results of tests performed on 35 materials, including woods, synthetic and textile materials, which have been submitted to thermal degradation at three different combustion temperatures. In addition, the interpretation and limitations of toxicological test results are discussed more generally. INTRODUCTION -~Although fire fighting techniques have greatly developed and improved over the years and although the way in which buildings are designed as well as the types of materials available to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, Herpol did not observe any animal deaths until a temperature of 600°C was reached [37]. This may reflect a difference in material concentration, formulation, or any number of possible variations in the experimental conditions.…”
Section: Din 53 436 Methods -Federal Republic Of Germanymentioning
confidence: 88%
See 1 more Smart Citation
“…However, Herpol did not observe any animal deaths until a temperature of 600°C was reached [37]. This may reflect a difference in material concentration, formulation, or any number of possible variations in the experimental conditions.…”
Section: Din 53 436 Methods -Federal Republic Of Germanymentioning
confidence: 88%
“…This may reflect a difference in material concentration, formulation, or any number of possible variations in the experimental conditions. Herpol [37] demonstrated an increase in the CO and slight decrease was evident when the temperature was further increased to 800°C (see Table 11). In pure CO experiments, Herpol [37] found that the CO index necessary to cause death during a 30 minute exposure was 120,000 ppm*min (equivalent to a 30 minute exposure to A, 000 ppm).…”
Section: Din 53 436 Methods -Federal Republic Of Germanymentioning
confidence: 99%
“…In one study, samples of a self-extinguishing rigid polyurethane foam (K14), coated with asbestos on both sides, were degraded at three different temperatures, 400,600 and 800 0C. 54 An air flow of 2001 h-' was maintained through the furnace and the combustion products in the exposure chamber were further diluted with an additional air flow of 2001h-'. Rats were exposed in a whole-body mode for 30min and lethality (as measured by the cessation of respiration) was the biological endpoint.…”
Section: Din Toxicity Test Methodsmentioning
confidence: 99%
“…The T X value for the selfextinguishing rigid polyurethane foam (K14) was 18.00 at 600°C, which places it in the lower 50% of the range of values found for the materials studied. 54 The maximum T X values for the untreated (K5) and self-extinguishing polyurethane foam (K6) were 75.7 (700°C) and 44.4 (500 "C), respectively, which are in the upper 50% of the range of values.56 Foam (K6), however, appeared to be less dangerous than the non-fire retarded polyurethane foam (K5) based on a 'global toxicity index'(an expanded mathematical model of the T X developed by Herpol).…”
Section: Din Toxicity Test Methodsmentioning
confidence: 99%
“…Herpol and Vandevelde [39,40] also tested polystyrenes according to the procedure outlined above for Herpol [38]. They did not report their raw data.…”
mentioning
confidence: 99%